Genome-wide Analysis of CONSTANS-like (CqCOL) Transcription Factors in Quinoa (Chenopodium quinoa): Structural Diversity, Phylogeny, and Stress-Responsive Expression - Tran, Huyen Thi Thanh; Dong, Gioi Huy; Chu, Ha Duc; Cao, Phi Bang (HAYATI Journal of Biosciences, 2025)
Quinoa (Chenopodium quinoa) is an ancient grain renowned for its remarkable nutritional value and remarkable adaptability to diverse environmental conditions, making it a valuable crop for enhancing food security. Understanding the molecular mechanisms triggering its development and stress responses is crucial for crop improvement. This study conducted a comprehensive analysis of the CONSTANS-like (CqCOL) transcription factors in quinoa, which play a pivotal role in photoperiodic flowering regulation. We identified and characterized 20 CqCOL genes, analyzing their physicochemical properties, phylogenetic relationships, gene structures, and promoter regions. Our findings revealed significant diversity among the CqCOL proteins and suggested potential functional specialization within the family. Promoter analysis uncovered various stress-responsive and phytohormone-responsive cis-regulatory elements, revealing that CqCOL genes may be associated with stress adaptation and hormonal signaling pathways. Transcriptomic analyses under different conditions supported these insights, highlighting the importance of CqCOL genes in quinoa's developmental processes and stress responses. Specifically, most CqCOL genes exhibited stable expression under heat stress, except CqCOL02 and CqCOL12, which were induced in roots by 1.85- and 1.91-fold, respectively. Under normal conditions, CqCOL01, CqCOL11, and CqCOL18 showed organ-specific expression, particularly in flowers and leaves, with no expression detected in roots. This study enhances our understanding of the CqCOL transcription factor family. It provides a foundation for future functional studies and breeding strategies aimed at improving stress tolerance and optimizing flowering time in quinoa.